“ Managing the household of God” Th e contribution from management sciences to the sustainability of the church as an organization - Oosthuizen, AJ; Lategan, LOK (Stellenbosch eological Journal, 2015)
Church leaders are considered “managers of the household of God” (1 Cor 4: 1, 2) and responsible to give the transforming message of the gospel its rightful place in the organization of the church as well as in the broader society. Despite this imperative, a literature review confi rmed that the church as an organization has not been studied extensively by management science, nor do faculties and institutions of theology engage properly with management science. Th e focus of this article is therefore twofold: to prove that basic management science principles and skills do apply to the church as an organization; and secondly, to identify some of the reasons why the church has not suffi ciently incorporated and applied management science principles and skills that can contribute to the eff ective management of the church. Th is article contributes to the management of the church as an organization. Although it is commonly acknowledged that diff erent churches and denominations deal with management in diff erent ways, the universality of management skills and principles apply to the church as organization in all its diff erent forms and contexts.
Published Article
Keywords: Management science; household of God; church as an organization; management; leadership; administration